THE DETERMINATION OF THE APPEARANCE, COLOR, DENSITY OF ETHYL ACETATE OBTAINED ON THE BASIS OF EAF - Jumayeva Z.E; Mirzayeva F.J.; Saidov D.X (Scholar Express Journal, 2021)
Methods have been developed for the production of ethyl acetate, with the continuous interaction of acetic acid with ethyl alcohol in the presence of heterogeneous acid catalysts with simultaneous distillation of the resulting ethyl acetate at a temperature of 75-90 ° C. Ethyl acetate in appearance and color, density, mass fraction of the main substance, mass fraction of acids in terms of acetic acid, mass fraction of water corresponded to SS 8981-78
Keywords: Ethyl acetate; preparation of ethyl acetate from the ether-aldehyde fraction; ethanol; ethanol dehydrogenation catalysts